2022
DOI: 10.1177/08901171221076778
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of a Fruit and Vegetable Prescription Program in the Northern Manhattan Community

Abstract: Purpose This study aimed to assess whether produce prescription redemption was associated with food insecurity (FI), sociodemographics, and nutrition-related health measures, and to identify factors affecting participation. Design Retrospective, cross-sectional study. Patients, equally divided between groups who redeemed and did not redeem prescriptions, completed a follow-up survey. Setting Northern Manhattan, NY. Subjects 242 patients referred to Nutrition at an academic medical center between June and Novem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…Table 1 shows an overview of the included studies, and Table 2 provides more details on all of the studies included. A total of 21 studies were reviewed, including 13 (61.9%) food or produce prescription program studies [16][17][18][19][20][21][22][23][24][25][26][27][28][29], 4 (19.0%) medically tailored meal (MTM) program studies [5,[30][31][32], and 4 (19.0%) community-supported agriculture (CSA) studies [33][34][35]. Fifteen studies (71.4%) focused on adult populations and four (19.0%) focused primarily focused on families and pediatric populations.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Table 1 shows an overview of the included studies, and Table 2 provides more details on all of the studies included. A total of 21 studies were reviewed, including 13 (61.9%) food or produce prescription program studies [16][17][18][19][20][21][22][23][24][25][26][27][28][29], 4 (19.0%) medically tailored meal (MTM) program studies [5,[30][31][32], and 4 (19.0%) community-supported agriculture (CSA) studies [33][34][35]. Fifteen studies (71.4%) focused on adult populations and four (19.0%) focused primarily focused on families and pediatric populations.…”
Section: Resultsmentioning
confidence: 99%
“…In terms of the outcomes assessed (Table 3) in the 21 studies, 10 studies (47.6%) assessed changes in BMI, 17 examined changes in dietary intake (81.0%), 13 (61.9%) examined improvement in food security status, 14 (66.7%) measured improvements in participants' chronic conditions, 12 (57.1%) assessed feasibility-related outcomes, and 4 (19.0%) assessed cost-related outcomes. Of the 10 studies that assessed changes in BMI, 2 studies [27,32] found a statistically significant reduction in BMI, 7 [17,18,26,28,30,31,35] found non-statistically significant changes, and 1 [33] found an increase in BMI. For dietary intake in the 17 studies (81.0%), 9 (42.9%) found an increase in fruit and/or vegetable intake [19][20][21][22][23][24][25]28,32], and 5 (23.8%) found no statistically significant changes in this intake [19,26,31,33,34].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2 and results in Table 2 . Ten studies were quantitative, 39 41 , 45 , 46 , 48 , 49 , 51 – 53 five were qualitative, 42 , 44 , 50 , 54 , 55 and four used mixed methods. 43 , 47 , 56 , 57 Of the 14 quantitative or mixed methods studies, 13 were longitudinal and one was cross-sectional.…”
Section: Resultsmentioning
confidence: 99%